Calcium alginate microencapsulation of ovarian follicles impacts FSH delivery and follicle morphology - McGee Elizabeth A; Russell Alan J; Koepsel Richard; Heise Matthew (BMC, 2005)
Abstract Background We have previously shown that suspension culture prevents follicle flattening and maintains three-dimensional follicle architecture better than culture on flat plates. However, many of the follicles cultured in suspension do eventually rupture, as basement membrane integrity is lost and the three-dimensional structure of the follicle is altered. Therefore, the objective of this study is to support three-dimensional follicle architecture during in vitro growth of ovarian follicles through encapsulation in calcium alginate, while maintaining responsiveness to FSH stimulation. Methods Preantral follicles (150 - 160 micrometers in diameter) were isolated from the ovaries of juvenile rats and grown in culture tubes or encapsulated in calcium alginate and grown in culture tubes. Previous studies revealed that follicles maintained structural integrity but did not grow as well when encapsulated in calcium alginate. In these studies, we evaluated the effect of calcium alginate on FSH-stimulated follicle growth, survival, and morphology in suspension culture. Follicles were grown under 5 culture conditions: 1) not encapsulated; with FSH in the medium, 2) encapsulated in the absence of FSH, grown in medium without FSH, 3) encapsulated with calcium alginate containing FSH but grown in medium without FSH, 4) encapsulated without FSH but grown in medium containing FSH and 5) encapsulated with calcium alginate containing FSH and in medium containing FSH. To assess growth rates, follicles were cultured for 72 hours and analyzed for follicle size increase and DNA content. Survival analysis for encapsulated and unencapsulated follicles was performed by constructing a Kaplan Meier survival curve of daily observations of intact follicle survival. Three-dimensional architecture was assessed histologically and by analysis of the pattern of connexin 43 expression in the cultured follicles. Results In the absence of FSH, follicle diameter increased by only 6.4%. When FSH was included in the alginate bead alone or the media alone, the follicle diameter increased by 13.5% and 19.9% respectively. This was greater than follicles cultured in the absence of FSH (p < 0.05), but less than that of the FSH-treated unencapsulated follicles (p < 0.05). However, when follicles were cultured with FSH included in both the media and the bead, a 32.6% increase in follicle diameter was observed, statistically no different than the growth rate of the unencapsulated follicles grown with FSH. Conclusion Microencapsulation supports three-dimensional follicle growth, but may limit access to hormones in the medium resulting in altered development compared to unencapsulated follicles. Inclusion of FSH in the alginate bead restores the follicle growth response to FSH, while also providing a scaffold of support for three-dimensional growth. The application of tissue engineering principles to the problems of follicle culture in vitro may provide advances applicable to fertility preservation in women and endangered species.